Quality of Researchers’ Searches of the ERIC Database - Hertzberg, Scott; Rudner, Lawrence (Education Policy Analysis Archives, 1999)
During the last ten years, end-users of electronic databases have become progressively less dependent on librarians and other intermediaries. This is certainly the case with the Educational Resources Information Center (ERIC) Database, a resource once accessed by passing a paper query form to a librarian and now increasingly searched directly by end-users. This article empirically examines the search strategies currently being used by researchers and other groups. College professors and educational researchers appear to be doing a better job searching the database than other ERIC patrons. However, the study suggests that most end-users should be using much better search strategies.